Pengaruh Harga, Promosi, dan Pengalaman Pelanggan terhadap Repurchase Intention pada Marketplace Shopee (Studi pada Gen Z dan Milenial Kabupaten Magetan) - Neo Agil Manova; Budi Wahono; Ety Saraswati (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of Price, Promotion, and Customer Experience on Repurchase Intention among Shopee marketplace users from Generation Z and Millennials in Kabupaten Magetan, using a quantitative approach through questionnaires administered to 75 respondents who had made more than one transaction. The study employed purposive sampling and data were analyzed using instrument testing, classical assumption tests, multiple linear regression, t-test, and F-test with SPSS. The results indicate that collectively, the three variables have a positive and significant effect on Repurchase Intention; however, partially, only Price and Customer Experience are significant, with Price identified as the most dominant variable. This confirms that appropriate pricing and satisfying shopping experiences are key factors in increasing repurchase intention among young consumers in non-metropolitan areas. Keywords: Price, Promotion, Customer Experience, Repurchase Intention, Shopee.